2016
DOI: 10.1016/j.ijrobp.2015.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic Vertebral Body Irradiation Contributes to Acute Hematologic Toxicity During Chemoradiation Therapy for Non-Small Cell Lung Cancer

Abstract: Purpose To determine the relationships between radiation doses to the thoracic bone marrow and declines in blood cell counts in non-small cell lung cancer (NSCLC) patients treated with chemoradiation therapy (CRT). Methods and Materials We included 52 patients with NSCLC treated with definitive concurrent carboplatinepaclitaxel and RT. Dose-volume histogram (DVH) parameters for the thoracic vertebrae (TV), sternum, scapulae, clavicles, and ribs were assessed for associations with changes in blood counts duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 39 publications
(39 reference statements)
0
40
1
1
Order By: Relevance
“…However, the dosimetric constraints of the ribs should also be taken into consideration. Moreover, our data revealed higher cut-off values for the MVD and TVV 20 than those reported by Deek et al 17 Several differences between the two studies included the cancer type, chemotherapeutic agents, irradiation doses and techniques, as well as thoracic vertebrae delineation. In our study, we delineated thoracic vertebrae from T1-T12 rather than T1-T10, which may lead to the determination of differing cut-off values.…”
Section: (Continued)contrasting
confidence: 76%
See 3 more Smart Citations
“…However, the dosimetric constraints of the ribs should also be taken into consideration. Moreover, our data revealed higher cut-off values for the MVD and TVV 20 than those reported by Deek et al 17 Several differences between the two studies included the cancer type, chemotherapeutic agents, irradiation doses and techniques, as well as thoracic vertebrae delineation. In our study, we delineated thoracic vertebrae from T1-T12 rather than T1-T10, which may lead to the determination of differing cut-off values.…”
Section: (Continued)contrasting
confidence: 76%
“…Data regarding the impact of different radiotherapy techniques on acute HT have been limited in patients with thoracic cancer. In a retrospective review, Deek et al 17 reported no statistically significant differences in the WBC nadirs among patients treated with 3D-CRT, IMRT or 3D-CRT/IMRT. Roeder et al 18 have also reported on their experience of using IMRT and concurrent systemic chemotherapy as a definitive treatment for locally advanced EC.…”
Section: (Continued)mentioning
confidence: 98%
See 2 more Smart Citations
“…Hence, selective sparing of pelvic osseous structures may be a viable option to decrease HT during concomitant CH-RT in anal cancer patients [9]. In several studies, a significant correlation between different dose-volume metrics and blood cell nadirs and/or HT was found [10][11][12][13][14][15]. Other than anal cancer, different clinical contexts were investigated such as cervical, rectal, lung and prostate cancer.…”
Section: Introductionmentioning
confidence: 99%